PENGARUH JARAK TANAM TERHADAP PRODUKSI TANAMAN TOMAT (Lycopersicum esculentum Mill) SEBAGAI SUMBER BELAJAR BIOLOGI SMA - Widayanti, Esti (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
The research was conducted in Notoharjo Trimurjo Lampung Tengah at January 10 2012 until April 05 2012. The purpose from the research were 1) to know the effect distance of plants with tomato productions. 2) to know the effect of distance of plants that more exact with tomato production. The population of the research was 96 tomato plant with 4 do it and 3 crop. The total sample of plant was bruoght 32 of tomato plants. The research was conducted by using experimental design especially Completed Randomized Design (RAL), and the data analysis by using ANOVA and BNJ test. In varians analys have the value from do it 5,97 >= 2,95 to warel of real level 0,05. So that push and received H1. And at BNJ test we can know average from other test A=1,5;B=1,37;C=1,75; and D=2. From this research we can know the congclution that (1) this have a influence of a plants with a tomato productions and (2) plant with using a plants distance 70 x 50 cm give a better influence with a plants tomato production. From the result the research can give an advantage to source of study biology at the growth and development material. Kata Kunci: jarak tanam, produksi tomat, sumber belajar biologi.